2007
DOI: 10.1016/j.annepidem.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis Among Women Exposed to Polybrominated Biphenyls

Abstract: Purpose-We examined the association between endometriosis and exposure to polybrominated biphenyls (PBBs) and polychlorinated biphenyls (PCBs) among women inadvertently exposed to PBBs in 1973.Methods-Serum PBB and PCB were measured in the late 1970s. Women self-reported endometriosis at interview in 1997. We constructed Cox models to estimate the relative incidence of endometriosis in relation to PBB and PCB levels.Results-Seventy-nine of 943 women (9%) reported endometriosis. Compared to women with low PBB e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 32 publications
1
25
1
Order By: Relevance
“…In the German Environmental Survey III of 1998, median urinary total arsenic levels in 4052 adults varied with seafood intake, had decreased since the prior 1990-1992 survey, and were about two-fold lower than those for the U.S. population in NHANES 2003(Schulz et al, 2007Caldwell et al, 2008). In a Nevada town where groundwater levels were naturally elevated, the median total urinary arsenic in about 200 people was approximately four times higher than that of the U.S. population (Rubin et al, 2007;Caldwell et al, 2008). Compared with this Report, higher mean or median total urinary arsenic levels have been reported among people living in specific western areas of North America (Calderon et al, 1999;Josyula et al, 2006;Meza et al, 2004;Valenzuela et al, 2005) and…”
Section: Biomonitoring Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the German Environmental Survey III of 1998, median urinary total arsenic levels in 4052 adults varied with seafood intake, had decreased since the prior 1990-1992 survey, and were about two-fold lower than those for the U.S. population in NHANES 2003(Schulz et al, 2007Caldwell et al, 2008). In a Nevada town where groundwater levels were naturally elevated, the median total urinary arsenic in about 200 people was approximately four times higher than that of the U.S. population (Rubin et al, 2007;Caldwell et al, 2008). Compared with this Report, higher mean or median total urinary arsenic levels have been reported among people living in specific western areas of North America (Calderon et al, 1999;Josyula et al, 2006;Meza et al, 2004;Valenzuela et al, 2005) and…”
Section: Biomonitoring Informationmentioning
confidence: 99%
“…Dioxin and other organochlorine chemicals have been shown to interfere with male and female reproductive development in experimental and wild animals, particularly during gestational exposure (Gao et al, 1999;Grey and Ostby, 1995;Roman et al, 1998;Sonne et al, 2006;Theobald et al, 1997). In studies of women with environmental or accidental exposures, associations between dioxin-like chemical exposures and various reproductive endpoints (Eskenazi et al, 2003;Lawson et al, 2004;Schnorr et al, 2001;Warner et al, 2004 and and endometriosis (Eskenazi et al, 2002;Fierens et al, 2003;Heilier et al, 2005;Hoffman et al, 2007) have been either absent or of unknown significance, though animal studies have demonstrated reproductive effects at high doses (Arisawa et al, 2005;U.S. EPA, 2004).…”
Section: Dioxin-like Chemicalsmentioning
confidence: 99%
“…There was an increased incidence of endometriosis among women in this cohort with moderate and high PCB levels compared to women with low PCB levels; however, PBB exposure was not associated with endometriosis. 3 In this study, we found that younger women were more likely to report a history of an abnormal Pap test. This may reflect the high prevalence of HPV and cervical dysplasia among younger women.…”
Section: Discussionmentioning
confidence: 49%
“…Birth weight and gestational age among offspring of women with the highest decile of PBB serum concentration, showed no significant association. Hoffman et al (2007) examined the association between endometriosis and exposure to PBBs (and PCBs) in 943 women of the Michigan cohort. Seventy-nine women (9 %) reported endometriosis.…”
Section: Effects On Fertility or Offspringmentioning
confidence: 99%